MEDAN MAKNA RASA PADA LIDAH DALAM BAHASA TOMBULU - Oldrie Ch. Sorey (Balai Bahasa Sulawesi Utara, 2011)
The research is aimed 1) to give the description about the genre and the total of lexemes in the taste bud of tongue in Tombulu language; 2) to give the description about the components of the taste bud of tongue in Tombulu language. The method in this research is descriptive, semantics theory is used to describe the meaning area. The results show that there are several lexemes found in the taste bud of tongue in Tombulu language. The lexemes are (1) delicious,‘ (2) plain; (3 ) bitter; (4) salty; (5) sweet; (6) not delicious; (7) rough; (8) sour.